Media and protest logics in the digital era : the Umbrella Movement in Hong Kong - Lee, Francis L. F. (Oxford studies in digital politics, 2018)
Digital and social media are increasingly integrated into the dynamics of protest movements around the world. They strengthen the mobilization power of movements, extend movement networks, facilitate new modes of protest participation, and give rise to new protest formations. Meanwhile, conventional media remains an important arena where protesters and their targets contest for public support. This book examines the role of the media -- understood as an integrated system comprised of both conventional media institutions and digital media platforms -- in the formation and dynamics of the Umbrella Movement in Hong Kong. For 79 days in 2014, Hong Kong became the focus of international attention due to a public demonstration for genuine democracy that would become known as the Umbrella Movement. During this time, twenty percent of the local population would join the demonstration, the most large-scale and sustained act of civil disobedience in Hong Kong's history -- and the largest public protest campaign in China since the 1989 student movement in Beijing. On the surface, this movement was not unlike other large-scale protest movements that have occurred around the world in recent years. However, it was distinct in how bottom-up processes evolved into a centrally organized, programmatic movement with concrete policy demands. In this book, Francis L. F. Lee and Joseph M. Chan connect the case of the Umbrella Movement to recent theorizations of new social movement formations. Here, Lee and Chan analyze how traditional mass media institutions and digital media combined with on-the-ground networks in such a way as to propel citizen participation and the evolution of the movement as a whole.